A New Structure of Random Approach Normed Space via Banach Space - Kream, Alaa A.; Hussein, Boushra Y. (Iraqi Journal of Science, 2024)
The goal of this research is to define the convergent sequence in A-random approach space and sequentially convergent are discussed and the cluster point, open and closed ball and linear transformation. We are going to explain a new structure of Random approach normed space via Banach space in and discussed all the relations between metric space in this research.